Efeitos da taurina na exposição repetida ao etanol em peixe-zebra: parâmetros comportamentais e atividade da monoamina oxidase cerebral - Stefanello, Flavia Vestena (2021)
Alcohol abuse is associated with negative health impacts including high mortality and morbidity rates, as well as induces several behavioral changes. However, drugs available to treat disorders related to alcohol use have low therapeutic efficacy and the search for new treatment alternatives is essential. Thus, taurine (TAU) appears as a potential target for study due to the pleiotropic action in the brain, which is involved in maintaining the integrity of the membrane, osmoregulation, neuromodulation, in addition to having antioxidant activity. Here, we investigate whether TAU plays a beneficial role against the effects of repeated ethanol (EtOH) exposure on different behavioral domains of zebrafish, especially focusing on social behavior, anxiety-like responses, memory and brain monoamine oxidase (Z-MAO) activity, since monoamines can play an important role in EtOH-mediated responses. In the present study, fish were exposed to non-chlorinated water or 1% EtOH for 8 consecutive days (20 minutes per day). From the fifth day, immediately after EtOH exposure, animals were exposed in the absence or presence of TAU (42, 150 or 400 mg/L) 1 hour per day (totalizing 4 exhibitions) until the end of the experiment period (eight day). Twenty four hours after the last exposure to EtOH (ninth day), fish were introduced to behavioral tests (shoaling behavior followed by the novel tank diving test or the inhibitory avoidance test) and biochemical assays were performed to evaluate the brain Z-MAO activity. We observed that TAU 150 abolished the responses induced by the repeated exposure protocol to EtOH, while the other concentrations tested showed a modest attenuation of this socially measured anxiety-like effect in zebrafish. Moreover, animals repeatedly exposed to EtOH showed increase in anxiety-like behaviors in the novel tank test, while TAU 42 and TAU 400 attenuated some behaviors responses. In the inhibitory avoidance test, TAU 42 and TAU 150 exerted a protective role by reversing the memory acquisition deficit caused by EtOH. Biochemical analysis revealed that TAU did not modulate the increase in brain Z-MAO activity induced by repeated EtOH exposure. Overall, our results show a potential beneficial effect of TAU against repeated EtOH exposure in zebrafish, reinforcing the growing utility of this model organism in scientific research to investigate the mechanism underlying the neurobehavioral responses of EtOH and TAU in vertebrates.